Unveiling the Hidden Truth: The Evolution and Advancement of Forensic Accounting in Indonesia - Ika Sari Wahyuni TD; Yuserrie bin Zainuddin; Hasnah Haron (proletargroup PT. Berbagi Teknologi Semesta, 2025)
Non-Indexed Publication